PLC BASED TRANSFORMER FAULT DETECTION AND PROTECTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Power and distribution transformers of substation are one of the most bloated and inexpensiveequipment in power system network. The protection of this equipment is the major issue and this issue overcomes by the give proposed system. In a power system has an enormous number of transformers and different components over an extended area in power systems network. Monitoring, data acquisition system and automatic controlling are the important problems in a power system this problems over come by using programmable logic controllers. This paper presents design and implementation of automatic control circuits which is used in PLC (programmable logic controllers) automation to observe as well asrectify fault of transformers like temperatures of the transformer, load currents, and voltages. The proposed on-line monitoring system combinesa solid state device named PLC and a various sensor packages. The suggested PLC monitoring system will help to detectinside fault as well as outside fault of transformer and also rectify these faults with the help of desired range of parameters which is set by programmer operating person who is on the desk of control panel.